1964
DOI: 10.1128/jb.88.2.361-366.1964
|View full text |Cite
|
Sign up to set email alerts
|

METABOLISM OF MEVALONIC ACID BY LACTOBACILLUS PLANTARUM

Abstract: Lactobacillus plantarum strain 8014-H2, unlike other lactobacilli studied, does not require mevalonic acid for growth, but growing and resting cells utilize it only for the synthesis of nonsaponifiable lipids. Upon the incubation of washed cells with mevalolactone-2-C14, the label appeared in the lipids but not in CO2. On the other hand, when mevalolac

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
10
0

Year Published

1966
1966
2012
2012

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 10 publications
0
10
0
Order By: Relevance
“…MATERIALS AND METHODS Growth of cells. Stock cultures of L. plantarum (ATCC 8014) were maintained on the semisynthetic medium of Skeggs et al (22) as previously described (7). A 0.1-ml amount of this culture was inoculated into 10 ml of Wright and Skeggs' medium (24) supple-mented with biotin (0.1 jtg/ml) and 0.5% maltose instead of glucose.…”
mentioning
confidence: 99%
“…MATERIALS AND METHODS Growth of cells. Stock cultures of L. plantarum (ATCC 8014) were maintained on the semisynthetic medium of Skeggs et al (22) as previously described (7). A 0.1-ml amount of this culture was inoculated into 10 ml of Wright and Skeggs' medium (24) supple-mented with biotin (0.1 jtg/ml) and 0.5% maltose instead of glucose.…”
mentioning
confidence: 99%
“…This procedure permitted the addition of a wide range of 14C-labelled compounds to the culture medium without initial dilution of radioactivity save by the small intracellular pools introduced with the inoculum. The results for the incorporation of 14C from a range of potential precursors into the thiamine moieties are collected in Table 1. All the 14C-labelled substrates supplied were well incorporated into the cells apart from [2-14C]mevalolactone and [2-14C] mevalonate, though the openchain formwas better incorporated than the lactone, as has been found in other systems (Fumagalli, Grossi, Poggi, Paoletti & Garattini, 1962;Durr & Shwayri, 1964). Also, DL-[3,4-14C2] methionine was less well incorporated than L-[Me-14C]methionine into the cells: this effect may be partly due to lack of transport of the D-enantiomer through the cell wall.…”
Section: Resultsmentioning
confidence: 55%
“…However, the distribution of radioactivity was reversed when DL-[2-14C]mevalonolactone was used, thereby suggesting that mevalonic acid is decarboxylated, presumably via the mechanisms operative in other mammalian tissues and bacteria (PopjAk & Cornforth, 1960). Durr & Shwayri (1964) have shown that for every mole of labelled carbon dioxide liberated from [1-l4C]mevalonolactone, lg.atom of labelled carbon was incorporated from [2-14C]mevalonolactone into the non-saponifiable lipids of Lactobacillus plantarum. This stoicheiometry in the metabolism of mevalonolactone by lactobacilli could not be demonstrated in adipose tissue.…”
Section: Discussionmentioning
confidence: 99%
“…Cholesterol, lanosterol and related sterols were obtained from Mann Research Laboratories, New York, N.Y., U.S.A. Alumina suitable for chromatography was obtained from E. Merck A.-G., Darmstadt, Germany. Buffers were prepared as described by Durr & Cortas (1964).…”
Section: Chemicals Dl-[14c]mevalonolactone Was Obtained Frommentioning
confidence: 99%
See 1 more Smart Citation